Mobile-Assisted Project-Based Learning using Plotagon Digital Animation for Teaching English to Nursing Students - Utomo, Dias Tiara Putri; Ryandini, Elda Yulia (Teaching English as Foreign Language, Literature and Linguisticss, 2025)
In the modern healthcare environment, nurses must be proficient in both spoken and written English to achieve better career prospects and ensure successful participation in continuing professional development. However, teaching English to nursing students in Indonesia has presented significant challenges like low motivation, lack of exposure, and lack of confidence in communication. The current research aims to students’ experiences and perceptions regarding the implementation of mobile-assisted project-based learning using Plotagon digital animation app. The phenomenological research was carried out in a Nursing Department in March-April 2025, involving fifteen students. The data were obtained through in-depth interview and analyzed by using data analysis spiral. The results indicated that the students perceived mobile-assisted project-based learning using Plotagon can encourage interactive and enjoyable learning, develop their language skills, facilitate creativity and critical thinking, promote group collaboration & engagement, and provide accessibility & flexibility. However, they also noticed possible improvement in terms of project implementation such as limited time to do the project and required reflection or discussion session once the project completed. By refining these aspects, Plotagon-based learning can further maximize student engagement, language proficiency, and creativity in English education.